Use of the Language Power in Law Enforcement: A Forensic Linguistic Review - Oktaviani, Adelia; Marbun, Rocky; Bambang Hermanto, Asep (KnE Social Sciences, 2024)
This article aims to increase knowledge and insight into the language of power in law enforcement. Media is a means of communication to convey a message or opinion to a large audience. The language commonly used in the media often looks a little impolite or even tends to be rude. It seems that people pay less attention to the language used, hence they are not aware that their words or writing may be demanded by other readers. In this research, a qualitative descriptive method is used semantically, because the writer focuses on researching the meanings of the language used. In this case, what is meant by focusing on the meaning of research is that this research will interpret the data one by one to get the results of the research. Research data is limited to one source, namely the Novel (Dari Balik Lima Jeruji). This research is forensic linguistic research and was analyzed combining two ways, namely linguistically and legally. Linguistic analysis in this study is only limited semantically, while legal analysis uses the law. The results of this study show that there is an abuse of the language of power by law enforcement officials in upholding the law. Keywords: media, linguistic, forensic, dispensation of justice